2003
DOI: 10.1046/j.1439-0434.2003.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Phytophthora citricola on Rhizosphere Soil Solution Chemistry and the Nutritional Status of European Beech Seedlings

Abstract: In a rhizotron experiment the influence of Phytophthora citricola on root development, rhizosphere chemistry and nutritional status of beech seedlings was studied. After infection, the fine root system was seriously damaged and 6 weeks after inoculation some seedlings died. Plants infected with Phytophthora citricola had less steep concentration gradients of K+, Ca2+, Mg2+ and NO in the rhizosphere soil solution as compared with uninfected seedlings, which indicates reduced activity in nutrient uptake. It is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…These investigations showed that P. citricola transiently reduced carbon assimilation of beech. Furthermore, P. citricola infection diminished the uptake of mineral nutrients as well as the nutrient status of leaves (Fleischmann et al 2004;Wang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These investigations showed that P. citricola transiently reduced carbon assimilation of beech. Furthermore, P. citricola infection diminished the uptake of mineral nutrients as well as the nutrient status of leaves (Fleischmann et al 2004;Wang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…P. citricola is a commonly isolated pathogen in central Europe with a broad range of economically important hosts such as Q. robur and Q. petraea (Jung et al ., 2000; Thomas et al ., 2002) and F. sylvatica (Jung et al ., 2005; Nechwatal and Oβwald, 2001; Wang et al ., 2003; Werres, 1995). P. citricola was the most frequently isolated Phytophthora species on beech trees in Europe (Jung et al ., 2005; Nechwatal and Oβwald, 2001) and during extensive surveys to monitor P. ramorum in England and Wales was also the most frequently isolated Phytophthora species from rhododendron leaves (Hughes et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hence in this study a decreased SRL may rather indicate a decreased nutrient uptake by fine roots than decreased nutrient availability. Wang et al (2003) showed that P. citricola infestation reduced nutrient uptake by fine roots of beech seedlings. The decrease in root morphological parameters due to P. citricola infection in the 20-40 cm deep slice was contrasted by an increase in root biomass that was also observed between 60 and 100 cm depth.…”
Section: Root Morphologymentioning
confidence: 99%